High Interest in Preexposure Prophylaxis Among Men Who Have Sex With Men at Risk for HIV Infection: Baseline Data From the US PrEP Demonstration Project. (1st April 2015) - Cohen, Stephanie E.; Vittinghoff, Eric; Bacon, Oliver; Doblecki-Lewis, Susanne; Postle, Brian S.; Feaster, Daniel J.; Matheson, Tim; Trainor, Nikole; Blue, Robert W.; Estrada, Yannine; Coleman, Megan E.; Elion, Richard; et al.
Abstract : Background: Preexposure prophylaxis (PrEP) is the first biomedical intervention with proven efficacy to reduce HIV acquisition in men who have sex with men (MSM) and transgender women. Little is known about levels of interest and characteristics of individuals who elect to take PrEP in real-world clinical settings. Methods: The US PrEP Demonstration Project is a prospective open-label cohort study assessing PrEP delivery in municipal sexually transmitted disease clinics in San Francisco and Miami and a community health center in Washington, DC. HIV-uninfected MSM and transgender women seeking sexual health services at participating clinics were assessed for eligibility and offered up to 48 weeks of emtricitabine/tenofovir for PrEP. Predictors of enrollment were assessed using a multivariable Poisson regression model, and characteristics of enrolled participants are described. Results: Of 1069 clients assessed for participation, 921 were potentially eligible and 557 (60.5%) enrolled. In multivariable analyses, participants from Miami (adjusted Relative Risk [aRR]: 1.53; 95% confidence interval [CI]: 1.33 to 1.75) or DC (aRR: 1.33; 95% CI: 1.2 to 1.47), those who were self-referred (aRR: 1.48; 95% CI: 1.32 to 1.66), those with previous PrEP awareness (aRR: 1.56; 95% CI: 1.05 to 2.33), and those reporting >1 episode of anal sex with an HIV-infected partner in the last 12 months (aRR: 1.20; 95% CI: 1.09 to 1.33) were more likely to enroll. Almost all (98%) enrolled participants were MSM, and at baseline, 63.5% reported condomless receptive anal sex in the previous 3 months. Conclusions: Interest in PrEP is high among a diverse population of MSM at risk for HIV infection when offered in sexually transmitted disease and community health clinics. Abstract : Supplemental Digital Content is Available in the Text.